Built-up structural steel sections as seismic metamaterials for surface wave attenuation with low frequency wide bandgap in layered soil medium. (1st June 2019) - Muhammad; Lim, C.W.; Reddy, J.N.
Highlights: Built-up steel sections as seismic metamaterial is studied. Attenuation of surface waves is reported in single and six layered soil medium. Low frequency wide bandgaps with relative bandwidth greater than 1.5 is achieved. The competency of bandgaps is validated by frequency and time domain analyses. More than 50% wave signal amplitude reduction is observed. Abstract: The purpose of this work is to investigate the propagation of surface waves through periodically arranged built-up steel section (resonator) in single and multiple layered soil medium (substrate) and to study the feasibility of surface waves attenuation by finite element technique. Two types of simple and small geometric size built-up sections are taken into consideration. Due to occurrence of local resonance between resonator and surface waves propagating on the surface of semi-infinite substrate, low frequency wide bandgaps are reported. Generation of local resonance is mainly governed by (i) impedance mismatch between the resonator and substrate (ii) coupling of longitudinal resonance modes of resonator with surface waves propagating on the surface of semi-infinite substrate. To have a more general and realistic study, surface wave propagation in single and six-layered soil medium is considered and the bandgaps are compared. Furthermore, with the variation in geometrical configuration of built-up section and change in material properties (soil profile), bandgap width and location changes. In the case of a layered soil medium, a relative bandwidth greater than 1.5 for both types of resonator is achieved. This implies that the proposed built-up sections are capable of attenuating surface waves in an extremely low frequency range. The position and width of bandgaps are further validated through finite unit cell based frequency response and time transient analyses. The findings substantiate the infinite unit cell model proposed here with the conclusion of more than 50% reduction in surface wave amplitude. The feasibility study manifests that the built-up structural steel sections can be applied as resonant barriers for mitigating seismic waves to protect important civil infrastructures from earthquake hazards.